Remote sensing & GIS applications - Pirasteh, Saied; Mahmud, Ahmad Rodzi; Mahmoodzadeh, Amir (Universiti Putra Malaysia Press, 2009)
Scientists, geologists and technologists will find this book as an invaluable references on the latest advances and applications of satellites in earth sciences studies. This practical book reflects on the applications of geoinformation technology (i.e. remote sensing integrated with GIS technology). It highlights various areas of earth sciences, geohazards, mapping, management, planning, early warning system and development that have been highly rewarding. These areas for geohazards include landslides, earthquake, tsunami, flood, cyclone, and typhoon as well as others.The first chapter deals with the general statement of the geohazards and challenges with emphasis on UNESCAP and examples of disasters with developing spatial data infrastructure. The second chapter enumerates the type of the disasters and its principle with causes in general; and highlights landslides, rock falls emphasis on stability and instability. the third and fourth chapters will discuss tectonic geomorphology and structural mapping practically in zagros mountain Iran, respectively. Chapter five discusses about the methodology to extract instability prone zone using river profiles. Tsunami is one of the disasters that has been discussed in chapter six. Chapter seven of this book is the technical paper that authors tried to emphasis the use of hydroinformatics throughout giving a technical paper from expertise. this book is useful for academia, a practical guide to the government and industry for development programs and plans as well as for further global research.